Perturbations in the impact of mutational activity on Vλ genes in systemic lupus erythematosus - Dörner, Thomas (BioMed Central, 2001)
To assess the impact of somatic hypermutation and selective influences on the Vλ light chain repertoire in systemic lupus erythematosus (SLE), the frequency and pattern of mutations were analyzed in individual CD19(+) B cells from a patient with previously undiagnosed SLE. The mutational frequency of nonproductive and productive rearrangements in the SLE patient was greater (3.1 × 10(-2) vs 3.4 × 10(-2), respectively) than that in normal B cells (1.2 × 10(-2) vs 2.0 × 10(-2), both P < 0.001). The frequencies of mutated rearrangements in both the nonproductive and productive repertoires were significantly higher in the patient with SLE than in normal subjects. Notably, there were no differences in the ratio of replacement to silent (R/S) mutations in the productive and nonproductive repertoires of the SLE patient, whereas the R/S ratio in the framework regions of productive rearrangements of normal subjects was reduced, consistent with active elimination of replacement mutations in this region. The pattern of mutations was abnormal in the SLE patient, with a significant increase in the frequency of G mutations in both the productive and nonproductive repertoires. As in normal subjects, however, mutations were found frequently in specific nucleotide motifs, the RGYW/WRCY sequences, accounting for 34% (nonproductive) and 46% (productive) of all mutations. These data are most consistent with the conclusion that in this SLE patient, the mutational activity was markedly greater than in normal subjects and exhibited some abnormal features. In addition, there was decreased subsequent positive or negative selection of mutations. The enhanced and abnormal mutational activity along with disturbances in selection may play a role in the emergence of autoreactivity in this patient with SLE.